FAKTOR-FAKTOR YANG MEMPENGARUHI CAPITAL ADEQUACY RATIO BANK UMUM TAHUN 2016-2023 - FEINA, DANIELLA; ARILYN, ERIKA JIMENA (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
The purpose of this research is to examine and obtain an empirical evidence from several variables that have an important role in banking sector, notably their influence toward bank capital ratio. These variables consist of Credit Risk, Liquidity, Profitability, Firm Size, and Debt Ratio. This research took data from 47 commercial banks that were actively listed on Indonesia Stock Exchange during the period 2016-2023. The technique that used in this research is purposive sampling. Seventeen commercial banks were selected according to the criteria and resulting 136 sample data. The collected data was analysis using multiple linear regression analysis methods. The result of this research indicates that Liquidity and Debt Ratio have negative effect on bank Capital Adequacy Ratio, Profitability and Firm Size have positive effect on bank Capital Adequacy Ratio, while Credit Risk have no effect on bank Capital Adequacy Ratio. The authors recommend several things which is, increasing the research data by adding a research period, reducing the sampling criteria, and adding other independent variables that related to strengthen the data for further research.